2018
DOI: 10.3390/ma11040568
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Gypsum on the Early Hydration of Cubic and Na-Doped Orthorhombic Tricalcium Aluminate

Abstract: The tricalcium aluminate (C3A) and sulfate content in cement influence the hydration chemistry, setting time and rheology of cement paste, mortar and concrete. Here, in situ experiments are performed to better understand the effect of gypsum on the early hydration of cubic (cub-)C3A and Na-doped orthorhombic (orth-)C3A. The isothermal calorimetry data show that the solid-phase assemblage produced by the hydration of C3A is greatly modified as a function of its crystal structure type and gypsum content, the lat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
23
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 40 publications
(61 reference statements)
5
23
0
Order By: Relevance
“…Regarding this stage, the work of Quennoz et al [1] reported that the remaining site for AFm nucleation on the surface of C 3 A controlled the acceleration part, and the space available for growth was the main factor impacting the slope of the deceleration part. Also, the result of Kirchheim et al [19] proved that only the reaction Equation (3) existed during this stage instead of the concurrence of Equations (1) and (3).…”
Section: Resultsmentioning
confidence: 98%
“…Regarding this stage, the work of Quennoz et al [1] reported that the remaining site for AFm nucleation on the surface of C 3 A controlled the acceleration part, and the space available for growth was the main factor impacting the slope of the deceleration part. Also, the result of Kirchheim et al [19] proved that only the reaction Equation (3) existed during this stage instead of the concurrence of Equations (1) and (3).…”
Section: Resultsmentioning
confidence: 98%
“…A clear inhibiting effect by nanosilica on C 3 A hydration was found in the above results. To further investigate the probable mechanism of the retarding phenomenon, the first step was to understand the influence of gypsum on C 3 A hydration, which was also shown an inhibiting effect and has been well studied 42‐46 …”
Section: Resultsmentioning
confidence: 99%
“…The high reactivity of this C 3 A-rich cement is not only due to the amount of C 3 A but also to the ratio cubic/orthorhombic C 3 A (0.7%/10.8%), controlled by the alkali content in the raw mix and the cooling rate [56]. In the presence of sulfate the orthorhombic C 3 A is more reactive than the cubic polymorph [57]. The low C 3 A cement, on the other side, forms smaller amounts of ettringite but, more important than that, it also increases strength at a slower pace.…”
Section: Discussionmentioning
confidence: 99%